Fetal colon diameter as a tool for estimating gestational age in advanced pregnancy in north Indian population: a pilot study - Arora, Renu; Punia, Nikky; Kumari, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Conventional Ultrasound dating is not very accurate after 34 weeks of gestation and has standard deviation of about 2 weeks. The aim of the study was to verify whether fetal colon diameter can be used as a tool for estimating gestational age (GA) of fetuses between 32 to 40 weeks. Methods: 100 healthy pregnant women aged 20-35 years were recruited. Fetal bi-parietal diameter, head circumference, abdominal circumference, and femoral lengths were assessed by ultrasound. In addition descending colon diameter was assessed at the level of colonic haustra. The correlation between GA and colon thickness was assessed by the Pearson correlation test. Results: Significant correlation between fetal colon diameter and maternal gestational age was observed (r=0.582). Correlation between gestational age and femur length (r = 0.725) was found to be higher than that between gestational age and colon diameter (r = 0.528) suggesting that femur length is a better parameter than colon diameter for gestational age estimation. The regression equation for gestational age as a function of colon diameter was derived as GA = 28.614 + 0.629 × CD. The diagnostic accuracy of CD of ≥ 12mm in predicting term pregnancy was 75% with a high negative predictive value of 88.9% and positive predictive value of 58.7%. Conclusions: The present study suggested that colon diameter can be used for predicting term pregnancy. Further studies are required to validate this novel marker of maturity amongst Indian population.